Income Disparity in Gerbangkertosusila Area of East Java Indonesia - Cahyono, Hendry; Subroto, Waspodo Tjipto; Anwar, Khoirul (International Journal of Economics and Financial Issues, 2017)
Based on the contribution of each of the cities in the region Gerbangkertosusila shows a striking difference between one and the other regions. Poverty and unequal income per capita differences also lead to the inequality in Gerbangketosusila. If in the gross inequality Gerbangkertosusila happen then it will affect the economy in the province of East Java in general and the northern part of East Java in particular. By knowing the causes through analysis of the potential sectors of the city in the region to GDP Gerbangkertosusila East Java province, then the potential sectors will be able to support the economic development in East Java. This study aimed to analyze the potential sectors and inequality in Gerbangkertosusila, attributable to the observation of programs and government policies promoting economic development in the province of East Java Williamson Index (IW). In Gerbangkertosusila has some potential sector that can support economic development along with the reduction of income inequality that occurred, manufacturing, mining, and agriculture. Of the existing sectors have the potential to be developed through a development priority programs along with policy direction to boost the economy in the northern part of the province of East Java Gerbangkertosusila the region. Keywords : income disparity, regional development, Gross Domestic Regional Product JEL Classifications: E01, R11